Law Enforcement of Cyber Pornography of Children on Social Media Based on Human Rights in Indonesia - Ritonga, Sheila Hamdah Hanum; Prasetyoningsih, Nanik (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Social media is beneficial as a medium of communication between users and users. Another advantage of social media is that it can expand relationships and knowledge. However, social media can be harmful if social media is used to damage, insult, and harass, which is why cyberporn emerged. Many children are perpetrators and victims of cyberporn on social media. This research aims to analyze cyberporn law enforcement on children on social media based on human rights in Indonesia. This research is normative research that looks at Legislation and cases. This research found that law enforcement in Indonesia is based on legal substance based on Law (U.U.) Number 19 of 2016 concerning Electronic Information and Transactions, Law No. 44 of 2008 concerning Pornography, Law No. 12 of 2022 concerning Crimes of Sexual Violence, the Criminal Code, and the Child Protection Law.